Growth? Well-being and quality of life! Opportunities and barriers to improve the institutional foundation of sustainable policies in Austria - Griesser, Markus; Brand, Ulrich (Momentum Quarterly, 2018)
In recent years, different sets of alternative indicators of societal wealth and progress have been developed by political actors on an international level, but also in different nation states. The point of departure of these projects is a critique of GDP and the effort to replace or to supplement it by (additional) indicators mainly concerned with social and ecological sustainability. Therefore, they can be conceived as entry points for a broader understanding of societal well-being and thus for quality of life and well-being oriented forms of policy-making. But even though numerous actors nowadays are providing such indicators, their political impact is rather limited. Hence, from the perspective of an interpretive policy analysis the article is asking for the strategic opportunities to improve the institutional foundation of sustainable policies in Austria.
Keywords: indicators of well-being; critique of GDP; alternative economic and social policies; quality of life and well-being oriented policies; interpretive policy analysis